▼Ticagrelor for acute coronary syndrome?. Issue 6 (1st June 2011) - Unknown
Abstract : Current guidelines from the National Institute for Clinical Excellence (NICE) recommend antiplatelet therapy comprising aspirin plus either clopidogrel or ▼prasugrel for patients with acute coronary syndrome (ACS).1, 2 However, such dual therapy increases the likelihood of bleeding compared to that with aspirin alone.3 ▼Ticagrelor (Brilique – Astra-Zeneca) is a new oral antiplatelet drug recently licensed in the UK (since publication of the NICE guidelines) for use with aspirin in patients with ACS, including those managed medically or undergoing percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG).4 Here we review the place of ticagrelor in the management of people with ACS, and whether it offers advantages over standard therapy in terms of greater efficacy or lower likelihood of bleeding complications.